Globalization, Migration and Xenophobia: An Investigation of the Issues, Challenges and the Way Forward - Agaigbe , Faeren Mercy; Akuraga, Fanen (Kashere Journal of Politics and International Relations, 2025)
This study examined the complex interrelationship between globalization, migration, and xenophobia in contemporary society. As globalization has intensified cross-border flows of people, goods, and ideas, international migration has increased significantly, often triggering xenophobic responses in receiving countries. This study investigates how economic integration, technological advancement, and cultural exchange which are key dimensions of globalization influence migration patterns and shape xenophobic attitudes. The study used secondary sources of data and employed the Social Identity Theory developed by Henri Tajfel and John Turner in the 1970s which posits that individuals categorize themselves and others into various social groups based on shared characteristics, such as nationality, ethnicity, religion, or cultural background as the framework for analysis. The findings reveal that while globalization has created unprecedented opportunities for mobility, it has simultaneously exacerbated inequalities that drive migration and fuel resentment toward immigrants. Economic insecurity, cultural anxiety, and political opportunism emerge as primary factors behind the rise of xenophobia. The study further identifies how xenophobic discourse and policies undermine social cohesion, violate human rights, and impede the potential benefits of migration. The investigation concludes that effectively addressing xenophobia requires a multifaceted approach that recognizes the structural causes of migration and the legitimate concerns of host communities. Recommendations include: Governments, civil society, and international organizations must work collectively to promote inclusive societies that embrace diversity. Initiatives aimed at combating discrimination, fostering intercultural dialogue, and celebrating the contributions of migrants can help reduce xenophobia.